Analogues of diadenosine 5',5'''-P1,P4-tetraphosphate (Ap4A) as potential anti-platelet-aggregation agents. - Zamecnik, P C (1992)
Dense granules of platelets contain a high content of diadenosine 5',5'''-P1,P4-tetraphosphate (Ap4A). We have previously demonstrated an antithrombotic effect of this compound in a live rabbit model. In the present study we find that certain synthetic Ap4A analogues are superior to Ap4A in inhibiting ADP-induced aggregation of human platelets. Analogues having a P--C--P bridge located in the P2,P3 position of Ap4A are the most potent inhibitors. These analogues are also resistant to hydrolytic enzymes. Analogues having the above characteristics exhibit competitive inhibition with ADP in the ADP-induced platelet aggregation reaction. These compounds, such as AppCHFppA, may be useful as antithrombotic agents. The analogues ApSppSpA and ApSpCHFpSpA also showed good inhibitory effects on ADP-induced platelet aggregation. In addition, this action of Ap4A and its analogues provides an example of a dinucleotide inducing an antagonistic effect by occupying an extracellular mononucleotide binding site on platelets. It calls attention to the possibility that Ap4A and its analogues may act in a similar way in whole organisms, triggering effector or inhibitory responses in any one of a variety of cells.